2000
DOI: 10.2527/2000.7861598x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin A injection before mating on oocyte development, follicular hormones, and ovulation in gilts fed high-energy diets.

Abstract: Previous research revealed that treatment with vitamin A approximately 5 d before ovulation may increase litter size in weaned sows and improve embryonal survival in gilts fed high-energy diets that reduced embryonal survival. For the current study, the hypothesis was that administration of vitamin A before ovulation would alter development of follicles and oocytes in a way favorable to enhanced embryonal survival. (Landrace x Large White) x (Duroc x Hampshire) gilts (n = 44) were fed 11.0 Mcal ME x gilt(-1) x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…The oocyte's developmental competence is enhanced by retinoid support during oocyte intrafollicular growth in the cow (Shaw et al, 1995), sheep (Eberhardt et al, 1999), and gilt (Whaley et al, 1997;Whaley et al, 2000), as in rabbits that have high levels of vitamin A (Besenfelder et al, 1996). In agreement with these findings, the addition of 9-cis-RA to in vitro maturation (IVM) cultures stimulated cortical granule migration in bovine oocytes both matured and meiotically arrested for a 24-hr culture period (Duque et al, 2002).…”
Section: Introductionmentioning
confidence: 57%
“…The oocyte's developmental competence is enhanced by retinoid support during oocyte intrafollicular growth in the cow (Shaw et al, 1995), sheep (Eberhardt et al, 1999), and gilt (Whaley et al, 1997;Whaley et al, 2000), as in rabbits that have high levels of vitamin A (Besenfelder et al, 1996). In agreement with these findings, the addition of 9-cis-RA to in vitro maturation (IVM) cultures stimulated cortical granule migration in bovine oocytes both matured and meiotically arrested for a 24-hr culture period (Duque et al, 2002).…”
Section: Introductionmentioning
confidence: 57%
“…It has been reported that the developmental competence of the oocyte is enhanced by ROH treatment in the cow (Shaw et al 1995), sheep (Eberhardt et al 1999) and gilt (Whaley et al 1997(Whaley et al , 2000, as well as in rabbits that have high blood levels of vitamin A (Besenfelder et al 1996). In studies involving cows (Shaw et al 1995), sheep (Eberhardt et al 1999) and gilts (Whaley et al 1997(Whaley et al , 2000 the effects of retinol on follicular development were monitored and recorded 4 days post-administration.…”
Section: Introductionmentioning
confidence: 99%
“…In studies involving cows (Shaw et al 1995), sheep (Eberhardt et al 1999) and gilts (Whaley et al 1997(Whaley et al , 2000 the effects of retinol on follicular development were monitored and recorded 4 days post-administration. The reason why these standards were set are not described and the limits (length and dosage) of ROH treatment are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mahan and Vallet (18) the stimulatory effect of various vitamins and minerals added to a feed on the sexual cycle of sows. A rapid growth and development of young growing gilts in their deficient diet during large-scale production could additionally affect the effect of increased weight of gilt's reproductive organs, which was achieved due to the administration of vitamin C. Vitamin C supplementation caused the increased levels of 17β-estradiol which influenced the growth and development of reproductive organs (6,40). Some authors (29,41) believe that backfat thickness above 16.0 mm is a prerequisite of good results in reproduction.…”
Section: Resultsmentioning
confidence: 99%